Efficiency improvement of indoor organic solar cell by optimization of the doping level of the hole extraction layer. (December 2020) - Biswas, Swarup; You, Young-Jun; Lee, Yongju; Shim, Jae Won; Kim, Hyeok
Abstract: Currently, the use of self- and low-powered, small dimension electronic devices for indoor use, such as smart meters, sensors, actuators, and wearable devices, is increasing our standard of living via the Internet of Things technology. Normal power sources are not recommended for these devices because of their small scale; however, an efficient means of powering them is via ambient energy harvesters. Indoor photovoltaic (IPV) cells are a very good power source option due to the ease of accessibility and availability of indoor light. Furthermore, IPV cells based on organic materials are one of the best options due to their good spectral matching and mechanical flexibility. Despite tremendous effort being devoted to the improvement of efficiency, applicability, longevity, and commercial acceptability of organic IPV devices, further research is needed to achieve their integrated use. In an organic IPV cell, the hole extraction layer (HEL) is an important component used to improve the hole extraction ability of the device. An alternative p-type semiconducting material that is cheaper, more environmentally stable, more processable, less sensitive to humidity, and highly conductive, is highly recommended. Therefore, in this work, we have attempted to develop a highly efficient organic IPV cell by optimizing the doping concentration of its HEL. We have used water-stable polyaniline (PANI) (doped with poly (sodium-4-styrenesulfonate) (PSS)) as the HEL because of its good environmental stability, low acidity, low price, and insensitivity to humidity. It has been observed that the indoor light energy harvesting ability of the device is strongly dependent on the doping concentration of its HEL and at an optimized concentration of PSS (100 mg), under the illumination of a 500 lx LED lamp; the device exhibits a power conversion efficiency value of 8.1%. Highlights: Water stable polystyrene sulfonic acid doped polyaniline is synthesized. The doping concentration of polyaniline is varied to control its physiochemical properties. Those materials are used as hole extraction layer (HEL) of organic indoor photovoltaic (IPV) device. The power conversion efficiency (PCE) of the IPV devices exhibit strong dependency on the doping concentration of their HEL. At optimized doping concentration of HEL, the IPV device shows higher PCE value (8.1%).